Evaluation of agricultural effluents and irrigation water as sources of antimicrobial resistant Escherichia coli - Romanis, Marco (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc Food Sc)--Stellenbosch University, 2013.